GRP-151 Program Interventions to Optimise the Duration of Antibiotic Treatment. (12th March 2013) - Aznarte, P; Hidalgo, C; Ferrit, M; Martínez, N; Pasquau, J
Abstract : Background: Reducing unnecessarily prolonged antibiotic treatment is one of the main initiatives to ensure the appropriate use of antibiotics. Purpose: To analyse the preliminary results of a pharmaceutical interventions programme trying to minimise the duration of antibiotic treatment, promoted within the antibiotics stewardship programme of a tertiary hospital. Materials and Methods: A protocol was agreed on by the antibiotics stewardship group, to capture via the Pharmacy Department antimicrobial treatments lasting more than 10 days made through the electronic prescribing programme. A pharmacist intervened to suspend or change these antibiotics treatments. We excluded: oncohaematology patients, treatments for urinary tract infections, endocarditis, diabetic foot, empyema, if Pseudomonas aeruginosa was detected or when it was impossible to confirm the type of infection. We analysed the results of interventions from 27 January to 17 July 2012. The following variables were examined: antibiotics involved, prescriber department, number of interventions, acceptance, indication for treatment and treatment at discharge. Results: A total of 111 interventions were carried out. The most commonly used antibiotics were: amoxicillin/clavulanic acid (15.3%), meropenem (13.5%) and levofloxacin (13.5%). The departments most involved were: Multipathological Care (43.2%), Internal Medicine (35.1%) and Pneumology (8.1%). 74.8% of the antibiotic treatments were initiated because of respiratory infection. 18.9% of patients maintained antibiotics at discharge. The range of overall duration of antibiotic treatment in respiratory infection ranged from 10 to 20 days. The overall acceptance of the interventions was: 65.8%. Within the accepted interventions, 68.5% caused antibiotic treatment to be suspended and 31.5% caused a change in the antibiotic used. Conclusions: The preliminary result of acceptance of interventions may be considered positive to ensure the programme is continued. To improve the acceptance of the interventions, it is necessary to increase involvement of Internal Medicine and Pneumology. The optimal duration of antibiotic therapy must assess the overall exposure, taking into account that established at the outpatient level. No conflict of interest.